2018
DOI: 10.1097/aud.0000000000000464
|View full text |Cite
|
Sign up to set email alerts
|

Chirp-Evoked Otoacoustic Emissions and Middle Ear Absorbance for Monitoring Ototoxicity in Cystic Fibrosis Patients

Abstract: The joint use of TEOAEs and absorbance has the potential to explain fluctuations in audiometric thresholds due to changes in cochlear function, middle ear function, or both. These findings are encouraging for the joint use of TEOAE and wideband absorbance objective tests for monitoring ototoxicity, particularly, in patients who may be too ill for behavioral hearing tests. Additional longitudinal studies are needed in a larger number of CF patients receiving ototoxic drugs to further evaluate the clinical utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…In tandem with other studies (Putterman et al, 2017;Garinis et al, 2017) using the present measurements system, the present work extended pressurized measurements of TEOAEs in adult ears up to a stimulus frequency of 8 kHz, which allowed the study of pressurization effects at higher frequencies compared to previous studies (as reviewed in Sec. I, previous studies extended to 5 kHz).…”
Section: Teoae Methodsmentioning
confidence: 65%
See 1 more Smart Citation
“…In tandem with other studies (Putterman et al, 2017;Garinis et al, 2017) using the present measurements system, the present work extended pressurized measurements of TEOAEs in adult ears up to a stimulus frequency of 8 kHz, which allowed the study of pressurization effects at higher frequencies compared to previous studies (as reviewed in Sec. I, previous studies extended to 5 kHz).…”
Section: Teoae Methodsmentioning
confidence: 65%
“…The inclusion criteria for their study was based on ages between 18 and 89 yrs, normal otoscopy, normal 226 Hz tympanometry including a TPP within 6100 daPa, and air-bone gaps of 10 dB or less between 0.5 and 4 kHz. Garinis et al (2017) reported that TEOAEs recorded at ambient and TPP had a generally similar performance in classifying ears as having normal hearing or a sensorineural hearing loss in a group of cystic fibrosis patients who had received ototoxic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The damage from these ototoxic drugs appears first at the basal end of the cochlea tuned to high frequencies, and includes damage to outer hair cells whose functioning is assessed via OAEs. Previous work demonstrated the potential value of TEOAEs to detect ototoxic SNHL in CF patients (Garinis et al, 2017b), but the upper TEOAE test frequency in that study was 8 kHz. This suggests the use of HF TEOAEs above 8 kHz as a potentially more sensitive diagnostic test for early identification of ototoxicity in CF patients.…”
Section: Methodsmentioning
confidence: 80%